Design and analysis of siloxanes removal by adsorption from landfill gas for waste-to-energy processes. (March 2018) - Elwell, Anthony C.; Elsayed, Nada H.; Kuhn, John N.; Joseph, Babu
Highlights: Removal of siloxanes by adsorption was simulated in 162 unique cases. Beds sized to have 6 months before breakthrough. Adsorbent, bed height, and siloxanes and moisture contents were varied. Process designed for moisture, siloxanes, and H2 S removal. Costs compared to LFG energy content and product value for the 3 WTE processes. Abstract: Separation of volatile methyl siloxanes from landfill gas using fixed adsorption beds was modeled with the objective of identifying appropriate technology and the economics associated with this purification step. A general adsorption model assuming plug flow and radial symmetry was developed and used to conduct a parametric sweep of 162 unique cases. The varied parameters were adsorbent type (activated carbon and silica gel), bed height (3.05–9.15 m/10–30 ft), inlet siloxane concentration (5–15 mg/m 3 ), moisture content (0–100% relative humidity at STP or RH), and siloxane tolerance limit (0.094–9.4 mg/m 3 ) that correlated to three distinct energy conversion technologies (electricity production using engines or fuels cells or catalytic conversion to liquid hydrocarbon fuels). Due to the detrimental effect of RH on siloxane absorption, the maximum allowable moisture content of LFG before purification is 50% RH and moisture removal processes are also required. The design calculations using a selected case study show that the adsorption bed height required needed for 6 months minimum breakthrough time for catalytic fuel production is twice that for engine applications. Fuel cell applications require 3 times the bed height compared to engine applications. However, the purification costs amounted to 94%, 16% and 52% of recovered product value for engine, liquefaction, and fuel cell applications, respectively indicating the need for a high value product to justify purification costs. The approaches and conclusions can be extended to specific process conditions for landfill gas purification and to other processes that use biogas produced from waste as a feedstock.